Effective Watershed Management Practices - Outcomes of the Watershed Science, Policy, Planning and Management Forum - Center for Natural Resources (EDIS)
This publication was produced by the Center for Natural Resources at the University of Florida. CNR 15 is part of a Program Summary Series. First published: 3/26/2002. Minor revision: March 2003.